Jenis-Jenis Strategi Pembelajaran - Melinda Saputri Pulungan; Nur Annisa; Vandawa Sipahutar; Muhammad Darwis Dasopang; Irwandi Sihombing (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Learning strategies play a crucial role in improving the quality of instruction and achieving educational objectives. The selection of appropriate learning strategies can help students develop critical thinking skills, social competencies, independent learning abilities, and problem-solving skills. This article aims to examine and analyze several student-centered learning strategies, namely Cooperative Learning, Problem-Based Learning (PBL), Information Search, and Inquiry. This study employed a library research method with a qualitative descriptive approach. Data were collected from various literature sources, including books, scientific journals, and other academic references related to learning strategies. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that each learning strategy possesses distinct characteristics and advantages. Cooperative Learning emphasizes teamwork and collaboration, Problem-Based Learning focuses on solving real-life problems, Information Search develops information literacy skills, while Inquiry promotes investigation and independent knowledge discovery. These strategies have been proven to enhance student participation, critical thinking, social skills, and learning autonomy. Keywords: learning strategies, cooperative learning, problem-based learning, information search, inquiry. Abstrak Strategi pembelajaran merupakan komponen penting dalam proses pendidikan yang berperan dalam meningkatkan kualitas pembelajaran dan pencapaian tujuan pendidikan. Pemilihan strategi pembelajaran yang tepat dapat membantu peserta didik mengembangkan kemampuan berpikir kritis, keterampilan sosial, kemandirian belajar, serta kemampuan pemecahan masalah. Artikel ini bertujuan untuk mengkaji dan menganalisis berbagai strategi pembelajaran yang berorientasi pada peserta didik (student-centered learning), yaitu strategi pembelajaran kooperatif, Problem-Based Learning (PBL), Information Search, dan Inquiry. Penelitian ini menggunakan metode studi pustaka (library research) dengan pendekatan deskriptif kualitatif. Data diperoleh dari berbagai sumber literatur berupa buku, jurnal ilmiah, dan referensi akademik yang relevan dengan strategi pembelajaran. Analisis data dilakukan melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa setiap strategi pembelajaran memiliki karakteristik dan keunggulan yang berbeda. Strategi kooperatif menekankan kerja sama kelompok, PBL berfokus pada pemecahan masalah nyata, Information Search mengembangkan kemampuan literasi informasi, sedangkan Inquiry menekankan proses penyelidikan dan penemuan pengetahuan secara mandiri. Keempat strategi tersebut terbukti mampu meningkatkan keaktifan peserta didik, kemampuan berpikir kritis, keterampilan sosial, serta kemandirian belajar. Kata kunci: Strategi Pembelajaran, Pembelajaran Kooperatif, Problem-Based Learning, Information Search, Inquiry.